Domestic Tourists' Revisit Intention: The Role of Novelty and Destination Image at Hidden Canyon Beji Guwang - Putu Gde Arie Yudhistira; Ni Kadek Reinita Andriyani; I Gede Agus Sukertha Yasa (Universitas Pendidikan Ganesha, 2022)
The uniqueness of natural tourism and new tourist experiences at Hidden Canyon Beji Guwang can attract tourists to visit this destination. The novelty aspect of the destination allows new experiences for tourists to stimulate their beliefs about the destination and influence the decision-making process. In addition, the destination's image is an essential factor that influences the intention of returning tourists. This study aims to analyze the effect of novelty and destination image on the intention to revisit domestic tourists at Hidden Canyon Beji Guwang. This research uses quantitative methods. Data from the online questionnaire survey was collected from 100 domestic tourists who had visited Hidden Canyon Beji Guwang from 2018 to 2021. The data analysis technique used was multiple regression analysis. Data were analyzed using SPSS Version 25.0. The test results show that the novelty of Hidden Canyon Beji Guwang partially has a positive and significant effect on the intention to revisit domestic tourists. The destination's image has a positive and significant effect on the intention to revisit domestic tourists at Hidden Canyon Beji Guwang. The novelty and the destination's image simultaneously have a positive and significant effect on the intention to revisit domestic tourists at Hidden Canyon Beji Guwang.